Treatment of pancreatic cancer with a combination of irinotecan (CPT-11) and gemcitabine: A multicenter phase II study by the Greek Cooperative Group for Pancreatic Cancer - Stathopoulos, G. P.; Rigatos, S.K.; Dimopoulos, M.A.; Giannakakis, T.; Foutzilas, G.; Kouroussis, C.; Janninis, D.; Aravantinos, G.; Androulakis, N.; Agelaki, S.; Stathopoulos, J.G.; Georgoulias, V. (Annals of Oncology, 2003)
Background: The efficacy and toxicity of gemcitabine (GEM) and irinotecan (CPT-11) is evaluated in previously untreated patients with inoperable or metastatic pancreatic cancer. Patients and methods: From January 1999 to July 2001, 60 patients with pancreatic cancer (85% stage IV) were enrolled in a two-step extended phase II trial. Patients were treated with gemcitabine (1000 mg/m2 on days 1 and 8) and CPT-11 (300 mg/m2 on day 8) in cycles of 3 weeks. No prophylactic use of recombinant human granulocyte colony-stimulating factor (rhG-CSF) was initially planned. Results: In an intention-to-treat analysis one (1.7%) complete and 14 (23.3%) partial responses were achieved [objective response rate (ORR) 24.7%; 95% confidence interval 14.04% to 35.96%]. Twenty-two (36.7%) and 23 (38.3%) patients had stable and progressive disease, respectively. The median duration of response was 5 months, the median time to tumor progression (TTP) was 7 months and the median overall survival 7 months. One-year survival was 22.5%. Pain improvement and asthenia during treatment were observed in 45% and 43% of patients, respectively; weight gain occurred in 19.5% of patients. Grade 3 anemia occurred in three (5%) patients who required transfusion of six packed red blood cell (RBC) units. Ten (16.7%) additional patients with grade 2 anemia were treated with recombinant erythropoietin. Grade 3 thrombocytopenia occurred in seven (11.7%) patients and grades 3 and 4 neutropenia in 27 (45%). Ten patients developed febrile neutropenia, two of whom died due to sepsis. Prophylactic use of rhG-CSF was eventually required in 93 (28.3%) of 329 administered cycles. Other toxicities were mild. Conclusions: The combination of gemcitabine and irinotecan is an active chemotherapy regimen against pancreatic cancer with a 25% ORR. Toxicity was acceptable for the great majority of patients but with a high percentage of hematopoietic growth factor administration.
Keywords: Combination; Gemcitabine; Irinotecan; Pancreatic cancer